Computational fluid dynamics of internal mammary artery–left anterior descending artery anastomoses. (24th October 2020) - Kanzaki, Tomohito; Numata, Satoshi; Yamazaki, Sachiko; Ikemoto, Koki; Hohri, Yu; Yaku, Hitoshi; Itatani, Keiichi; Nakajma, Shunsuke; Takahashi, Akihiko
Abstract: OBJECTIVES: The aim of this study was to elucidate the remodelling of the internal mammary artery (IMA)–left anterior descending artery anastomosis and compare 2 different anastomosis techniques (end-to-side versus side-to-side) using computational fluid dynamics. METHODS: This study included 9 patients. Computed tomography (CT) angiography was performed immediately after coronary artery bypass grafting (CABG) and at 3–6 months later. The computational fluid dynamics models were made using the CT data. The pulsatile 3-dimensional blood flow was achieved with the finite volume method to evaluate the postoperative morphological and haemodynamic changes at the anastomosis in each patient. Flow velocity distribution, wall shear stress (WSS) and its fluctuation oscillatory shear index were measured. RESULTS: No early or mid-term graft occlusion was observed in the study series. In the side-to-side anastomosis, pouch formation at the distal end of IMA caused a vortex flow with low WSS immediately after CABG. However, at 3–6 months after surgery, this pouch disappeared. As a result, the laminar straight flow with uniform WSS distribution was achieved inside the anastomosis. In the end-to-side anastomosis, the anastomosis shape was remodelled, resulting in a laminar flow pattern with uniform WSS distribution. A patchy high oscillatory shear index was detected at the IMA wall on the top of anastomosis in either anastomosis techniques immediately after the surgery, but it disappeared at 3–6 months after surgery. CONCLUSIONS: Regardless of the anastomosis technique used, a successful remodelling of the IMA–left anterior descending artery anastomosis shape was achieved a few months after surgery, resulting in a straightforward flow streamline, with uniform WSS distribution and minimal oscillatory shear index. Abstract : It is well known that the internal mammary artery (IMA) is remodelled after coronary artery bypass grafting (CABG) [1–3].